Bone healing after low-level laser application in extraction sockets grafted with allograft material and covered with a resorbable collagen dressing: a pilot histological evaluation. Issue 1 (December 2015) - Monea, Adriana; Beresescu, Gabriela; Tibor, Mezei; Popsor, Sorin; Antonescu, Dragos
Abstract Background Our aim was to determine whether low level laser therapy (LLLT) can decrease the time between extraction/socket graft and implant placement, by evaluating histological changes in sockets grafted with a particulate allograft material and treated with LLLT. Methods Thirty patients had a socket grafted with a particulate allograft material (MinerOss) covered with a resorbable collagen wound dressing. The patients were then randomly divided into two equal groups (n = 15): test group receiving postoperative LLLT treatment, and control group without postoperative laser treatment. The assessment of bone formation was carried out in both groups at well-determined time intervals after surgery by histostomorphometric analysis. Results The histological results of the site treated with LLLT for 21 days, harvested at 60 days after grafting showed abundant new bone formation without any sign of inflammation. The same results were obtained in the control group not before 120 days post-surgery. Conclusions It can be concluded that LLLT photobiomodulation can reduce the healing time after grafting the extraction socket. Histological evidence suggests that new bone formation in the sockets appeared within 60 days after LLLT treatment compared to a minimum of 120 days in the control group.